ANALISIS CO-CREATION EXPERIENCE SERTA DAMPAKNYA DALAM KONTEKS PARIWISATA - Kurniawan, Cahya Nova; Kusumawati, Andriani; Iqbal, Mohammad (PROFIT: JURNAL ADMINISTRASI BISNIS, 2020)
This literature review was aimed to determine what kind of antecedent factors thatformedtourism experience through co-creation activities.Our research was also  aimed to find out what kind ofoutcomes that generated after a tourist gained their experience from the co-creation processes. This research were utilized from various books and alsoseveral numbers of reputed indexed journals. From this literature review, researcher found that there were four factors that formed tourist’s experience by co-creation that called by interaction, participation, sharing and customization. Next,researcher found that therewere four impacts that raised from the process of co-creation experiences, such as satisfaction, feelings of proportion between expenditures and experiences that gained by tourists, happiness, and also memorable experiences. These literature review concluded  some implications for tourism providers to applied the concept of co-creation in case of  how to made an unique tourism experiences, so it canprovided added values for both parties